CyCLOPS: A Novel Strategic Research Infrastructure Unit for Continuous Integrated Spaced-based Monitoring of Geohazards - Danezis, Chris; Hadjimitsis, Diofantos G.; Eineder, Michael; Brcic, Ramon; Agapiou, Athos; Themistocleous, Kyriacos; Mendonidis, Evangelos; Christofe, Andreas; Tzouvaras, Marios (My University, 2019)
Cyprus, being located on the Mediterranean fault zone, exhibits a unique geodynamic regime since its tectonic evolution is driven by the interaction of the Eurasian and the African plate. Besides its seismological interest, Cyprus exhibits many active landslides and slope instabilities in areas of steep topography that pose an imminent threat for entire settlements, critical infrastructure, and cultural and natural heritage landmarks. To address these challenges, a novel strategic research infrastructure unit, abbreviated CyCLOPS, is being developed and established by Cyprus University of Technology in cooperation with the German Aerospace Agency (DLR). CyCLOPS will utilize novel space technologies, including cutting-edge European space missions, such as Galileo, Copernicus Sentinel and TerraSAR-X along with state-of-the-art processing techniques to monitor the effects of geohazards, such as earthquakes and landslides, and assess their impact on the built environment and cultural heritage landmarks. The latter will be achieved by the robust and continuous estimation of ground deformation and its velocity gradients at a national and regional level. The determination of deformation will be carried out by means of novel integrated GPS/GNSS and SAR techniques, rendering Cyprus a dedicated calibration and validation site for European space missions.
Keywords: GNSS; SAR; Natural Hazards; Networks; Infrastructure; Cyprus